(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
This article discusses environmental education for students, Eco-STEAM education, interdisciplinary and practical orientation of students, physical education, biology, geography, computer science, technology, visual arts, engineering thinking, imagination, collaboration, creative abilities, and the formation of interdisciplinary ecological culture through extracurricular independent learning.